2003
DOI: 10.1590/s0006-87052003000100020
|View full text |Cite
|
Sign up to set email alerts
|

Risco climático de quebra de produtividade da cultura do feijoeiro em Santo Antônio de Goiás, GO

Abstract: A caracterização de riscos climáticos para algumas culturas tem sido feita com modelos de simulação e para a cultura do feijoeiro (Phaseolus vulgaris L.) tem-se utilizado o CROPGRO-Dry Bean. Esse modelo calibrado e testado para a região de Santo Antônio de Goiás, GO, foi utilizado na análise de risco climático de quebra relativa de produtividade da cultura naquela região. Para as simulações utilizou-se a série de dados climatológicos (1978 a 1998), as características físicas, químicas e hídricas do solo local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 3 publications
3
9
0
13
Order By: Relevance
“…These values met crop water requirements during growing cycle found by some authors conducting experiments in Brazil (DANTAS NETO et al, 2005;NÓBREGA et al, 2001;SILVEIRA;. Additionally, Doorenbos and Kassam (2000) concluded that maximum bean yield is achieved when 300 to 400 mm is available during the cycle, depending on the local edaphoclimatic conditions.…”
Section: Rainfall and Irrigationsupporting
confidence: 64%
See 4 more Smart Citations
“…These values met crop water requirements during growing cycle found by some authors conducting experiments in Brazil (DANTAS NETO et al, 2005;NÓBREGA et al, 2001;SILVEIRA;. Additionally, Doorenbos and Kassam (2000) concluded that maximum bean yield is achieved when 300 to 400 mm is available during the cycle, depending on the local edaphoclimatic conditions.…”
Section: Rainfall and Irrigationsupporting
confidence: 64%
“…at 53 days after plant emergence, and by Bastos et al (2002). These values were lower than those found by Meirelles et al (2002). Measured LAI values presented in Tables 3 and 4 showed that LAI max values exhibited the same behavior, with 2.14 m at 55 days after sowing.…”
Section: Simulated and Measured Soil Moisture Behaviormentioning
confidence: 73%
See 3 more Smart Citations